Microwave-electrochemical formation of colloidal zinc oxide at fluorine doped tin oxide electrodes - Rassaei, L; Jaber, R; Flower, SE; Edler, K; Compton, R; James, T; Marken, F (2010)
Colloidal ZnO is obtained during microwave-enhanced electrochemical deposition experiments from an aqueous solution containing 0.1 M Zn(NO 3)2 and 0.02 M H2O2 via repetitive negative going potential cycles from 0.3 to -0.8 V vs. SCE. The effects of temperature and temperature gradients on ZnO electro-formation at fluorine doped tin oxide (FTO) electrodes are investigated with both a conventional thermostated bath system (isothermal) and an in situ microwave electrochemistry system (non-isothermal). Mainly electrodeposition of ZnO is observed in uniformly heated stagnant solution and predominantly the electro-formation of ZnO colloid is observed in the presence of microwave-induced temperature gradients in a flowing solution. For the ZnO colloid prepared via microwave activation, SAXS data suggests an average particle radius of ca. 18 nm. The increase of ZnO nanoparticle concentration during repetitive potential scans is followed by photoluminescence spectroscopy. A possible mechanism for ZnO colloid formation during electrochemical reduction of H2O2 is suggested. © 2010 Elsevier Ltd. All rights reserved.